Therapeutic duplication on the general surgical wards - Isabelle Huynh; Tania Rajendran (BMJ Open Quality, 2021)
Therapeutic duplication is the practice of prescribing multiple medications for the same indication or purpose without a clear distinction of when one agent should be administered over another. This is a problem that occurs frequently, especially on electronic prescribing records (EPR) as the medication chart is not always reviewed before prescribing. The aim of this Quality Improvement Project (QIP) was to reduce therapeutic duplication to 0% through educating the general surgical team. Prescriptions of all general surgical patients in the surgical wards were reviewed daily for a month. EPR was used to check if there were any duplications or identical class of drug prescribed. Patient documentation was thoroughly checked to rule out if the duplication was intentional. Following this, if duplication was still unclear, the relevant teams would be contacted for clarification. Any unintentional error was removed, and data was collected. The QIP results were presented to the local general surgical meeting and our fellow colleagues were educated on the importance of safe prescribing and on how to prevent prescribing errors. The baseline of therapeutic duplications on the general surgical wards was 9% prior to our first cycle. Following the presentation of data and educating the surgical team at the surgical meeting, the number of errors seemingly reduced, however, there was a jump to 22% of therapeutic duplication on a particular Friday which brought the average of therapeutic duplication to 8.77%. The team was reminded again about the importance of correct prescribing and after the second cycle, the number of errors reduced to 5.29%. For the third audit cycle, the team was presented with the reaudited data and following this, the number of errors dropped down to 3.12%. Therapeutic duplication should never occur as this could cause a risk to patient harm. Through educating the surgical team and reminding our team regularly, the average number of errors reduced by more than half of the original number. In our hospital, the main source of safety net is through pharmacists and nurses, however as shown, this is not enough to prevent all therapeutic errors. A more sustainable intervention such as an alert on EPR prior to prescribing may be required to maintain a low therapeutic duplication average and prevent patient harm.